A modified characteristics projection finite element method for unsteady incompressible Magnetohydrodynamics equations - Shujie Jing; Jixiang Guan; Zhiyong Si (AIMS Mathematics, 2020)
This paper provides a modified characteristics projection finite element method for the unsteady incompressible magnetohydrodynamics(MHD) equations. In this method, modified characteristics finite element method and the projection method will be combined for solving the unsteady incompressible MHD equations. Both the stability and the optimal error estimates both in L2 and H1 norms for the modified characteristics projection finite element method will be shown. In order to demonstrate the effectiveness of our method, we will present some numerical results at the end.